2020
DOI: 10.1186/s12884-020-03302-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial status and prenatal care of unintended pregnancies among low-income women

Abstract: Background Nearly half of all pregnancies in the United States are reported as unintended and rates are highest among women of low socioeconomic status. The purpose of this study was to examine the associations between unintended pregnancies and maternal mental health and timing of prenatal care among low-income women. Methods In this cross-sectional study, 870 women, whom were participating in the First 1000 Days program in three community health centers in the Boston area, were enrolled at their first pren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Studies determined pregnancy intention by maternal self-report using measures from the PRAMS or measures modeled on the PRAMS; direct questions; and other approaches . Studies used various terms to elicit pregnancy intention from participants including whether the pregnancy was intended, wanted, planned, or mistimed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies determined pregnancy intention by maternal self-report using measures from the PRAMS or measures modeled on the PRAMS; direct questions; and other approaches . Studies used various terms to elicit pregnancy intention from participants including whether the pregnancy was intended, wanted, planned, or mistimed.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies reported adjusted estimates of the association between unintended pregnancy and maternal depression including 15 studies of depression during pregnancy (7 cohort and 8 cross-sectional studies) and 10 studies of depression post partum (4 cohort and 6 cross-sectional studies) (Table 1). For prenatal depression, 12 studies collected depression measures during pregnancy and 3 collected measures post partum .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, abortion bans are likely to change the composition of births in ways that will increase maternal mortality rates, rather than leaving them unchanged. Furthermore, less desired pregnancies -those most likely to end in abortion when it is available -are associated with lower levels of preventive care utilization and higher levels of stress and morbidity (Cruz-Bendezú et al 2020;Hall et al 2017;Kost and Lindberg 2015;Wolf et al 2015). Abortions are also sought because of a variety of health risks to pregnant people.…”
Section: Limitationsmentioning
confidence: 99%
“…In pregnant women, mental disorders are associated with socioeconomic status (SES) ( 12 , 14 , 17 , 18 ). In most studies, SES is associated with maternal age, smoking, educational attainment, income, and cohabiting ( 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%